2022
DOI: 10.1371/journal.pone.0263739
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary pathologies in the early phase of acute pancreatitis correlate with disease severity

Abstract: Background Respiratory failure worsens the outcome of acute pancreatitis (AP) and underlying factors might be early detectable. Aims To evaluate the prevalence and prognostic relevance of early pleuropulmonary pathologies and pre-existing chronic lung diseases (CLD) in AP patients. Methods Multicentre retrospective cohort study. Caudal sections of the thorax derived from abdominal contrast enhanced computed tomography (CECT) performed in the early phase of AP were assessed. Independent predictors of severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The sample sizes ranged from 25 to 909. Twenty-two studies [ 21 , 23 , 26–28 , 30 , 31 , 33 , 34 , 36–44 , 46–49 ] were from Asia, ten studies [ 16 , 17 , 20 , 22 , 25 , 29 , 32 , 35 , 45 , 50 ] were from Europe, and the rest [ 18 , 19 , 24 , 36 ] were from other regions. Among these studies, eleven studies [ 16–20 , 24 , 26 , 30 , 38 , 42 , 45 ] reported the location of PE, three studies [ 19 , 39 , 45 ] mentioned the size of PE, and five studies [ 20 , 23 , 32 , 35 , 42 ] provided data on mortality in AP patients with or without PE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes ranged from 25 to 909. Twenty-two studies [ 21 , 23 , 26–28 , 30 , 31 , 33 , 34 , 36–44 , 46–49 ] were from Asia, ten studies [ 16 , 17 , 20 , 22 , 25 , 29 , 32 , 35 , 45 , 50 ] were from Europe, and the rest [ 18 , 19 , 24 , 36 ] were from other regions. Among these studies, eleven studies [ 16–20 , 24 , 26 , 30 , 38 , 42 , 45 ] reported the location of PE, three studies [ 19 , 39 , 45 ] mentioned the size of PE, and five studies [ 20 , 23 , 32 , 35 , 42 ] provided data on mortality in AP patients with or without PE.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies [ 21 , 23 , 26–28 , 30 , 31 , 33 , 34 , 36–44 , 46–49 ] were from Asia, ten studies [ 16 , 17 , 20 , 22 , 25 , 29 , 32 , 35 , 45 , 50 ] were from Europe, and the rest [ 18 , 19 , 24 , 36 ] were from other regions. Among these studies, eleven studies [ 16–20 , 24 , 26 , 30 , 38 , 42 , 45 ] reported the location of PE, three studies [ 19 , 39 , 45 ] mentioned the size of PE, and five studies [ 20 , 23 , 32 , 35 , 42 ] provided data on mortality in AP patients with or without PE. Additionally, PE was detected by chest X-ray in eight studies [ 16 , 18 , 20 , 22–24 , 41 , 50 ], by CT in 14 studies [ 19 , 21 , 25–27 , 30 , 32 , 35 , 38 , 39 , 42 , 45–47 ], by transthoracic sonography in one study [ 17 ] and by combination of above methods in four studies [ 29 , 31 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pleural effusion is one of the common pulmonary complications in AP patients. The latest data show that the incidence of AP combined with pleural effusion is as high as 34%–54.5% 6,7 . The potential mechanisms of pleural effusion accumulation in AP are diverse and can be explained by the following reasons: inflammation‐induced changes in capillary permeability, diaphragmatic lymphatic obstruction, pleural‐pancreatic fistula formation, and sinus formation between the pleural cavity and PPC 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The latest data show that the incidence of AP combined with pleural effusion is as high as 34%–54.5%. 6 , 7 The potential mechanisms of pleural effusion accumulation in AP are diverse and can be explained by the following reasons: inflammation‐induced changes in capillary permeability, diaphragmatic lymphatic obstruction, pleural‐pancreatic fistula formation, and sinus formation between the pleural cavity and PPC. 8 Furthermore, up to 30%–40% of AP patients develop ascites, and a large proportion of patients develop mild to moderate ascites in the initial stage of inflammation, which may be secondary to local inflammation and subsequent transperitoneal and vascular exudation.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injury (ALI) is a life-threatening condition characterized by diffuse interstitial and alveolar edema resulting from the damage of pulmonary microvascular endothelial cells (PMVECs) and alveolar epithelial cells (AECs) [ 3 , 4 ]. ALI and its severe form, acute respiratory distress syndrome (ARDS), are among the most prevalent consequences of SAP and are leading causes of mortality in SAP patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%